Pemahaman Atas Investasi Memoderasi Pengaruh Motivasi dan Risiko Investasi Pada Minat Berinvestasi - Saraswati, Ketut Riandita Anjar; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 24 No 2 (2018), 2018)
ABSTRACT   This research is aimed to find out how the influence of understanding on investment in moderating the influence of motivation and investment risk on the interest of investing, by distributing kuisoner as much 121 to the respondent which is a nonreguler student of Faculty of Economics and Business Universitas Udayana with criteria of resopnden to fill the questionnaire is already take the course of capital market theory, in this research using data analysis technique of mutis mutation test and Internal Successive Method with nonprobability sample approach with purposive sampling technique. Based on the results of the analysis that has been done shows that the motivation has a positive effect on investment interest, investment risk has a negative effect on investment interest, investment understanding can strengthen the influence of motivation on investment interest and understanding of investment can strengthen the influence of investment risk on the interest of investing   Keywords: motivation, investment risk, investment understanding, and investment interest.